2018
DOI: 10.3390/catal8050188
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of N,N′-dialkylureas via Carbonylation of Amines with CO2 Applying Y0.08Zr0.92O1.96 Mixed Oxide (YSZ-8) as a Heterogeneous Catalyst

Abstract: Abstract:One-pot synthesis of N,N -dialkylureas were successfully achieved from catalytic carbonylation of aliphatic primary amines with CO 2 as the carbon source and Y 0.08 Zr 0.92 O 1.96 mixed oxide (Yttria-stabilized zirconia, YSZ-8) as the heterogeneous catalyst. The yield of the target product was obtained up to 80.60% from a 48 h reaction with an aliphatic primary amine and 3.0 MPa CO 2 in N-methyl-2-pirrolidinone at 160 • C. A multi-pronged mechanistic study was carried out where factors that might infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Among them, NMP is considered as the most preferable solvent for the carboxylation reaction to deliver 92.5% yield of 1,3-dihexylurea (1,3-DHU) due to its capability to trap CO 2 as well as its ability to stabilize the ionic intermediates (entry 12). [43,44] In contrast to NMP, alcohol solvents such as MeOH and 2-propanol (IPA), would reduce the basicity of the amines, and tend to compete with the amines for the nucleophilic attack to form carbamic acid intermediate during the reaction, [45] thus retarding the carboxylation process (entries 6 and 7). It is found that 13.2% yield of 1,3-DHU is achieved even in the absence of catalyst under identical conditions, showing that NMP solvent itself is able to promote the carboxylation reaction to some extent (entry 8).…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Among them, NMP is considered as the most preferable solvent for the carboxylation reaction to deliver 92.5% yield of 1,3-dihexylurea (1,3-DHU) due to its capability to trap CO 2 as well as its ability to stabilize the ionic intermediates (entry 12). [43,44] In contrast to NMP, alcohol solvents such as MeOH and 2-propanol (IPA), would reduce the basicity of the amines, and tend to compete with the amines for the nucleophilic attack to form carbamic acid intermediate during the reaction, [45] thus retarding the carboxylation process (entries 6 and 7). It is found that 13.2% yield of 1,3-DHU is achieved even in the absence of catalyst under identical conditions, showing that NMP solvent itself is able to promote the carboxylation reaction to some extent (entry 8).…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Regretfully, the high thermodynamic stability and kinetic inertness of the CO 2 molecule, compared to the relatively easy absorption and of capture CO 2 by amines, has hindered the synthesis of N , N ′-dialkylurea by the catalytic carbonylation of amines with CO 2 , especially with regard to the harsh reaction conditions required such as high temperature and high pressure. As a consequence, a series of efficient catalysts of thermal activation of CO 2 , including K-doped-δ-MnO 2 , MnO 2 , , Y 2 O 3 –ZrO 2 , CeO 2 , KOH/PEG, KOH, [bmim]­OH, Y 2 (C 2 O 4 ) 3 , Co­(acac) 3 , K 3 PO 4 , CsCO 3 , Sn–Ni–O, and 1,5-diazabicyclo[4.3.0]­non-5-ene (DBU) etc., have been developed and reported over the past ten years or so. Nevertheless, despite the progress being made in speeding up the reaction rate of the carbonylation of CO 2 with amine to produce N , N ′-dialkylurea, the desired advantages of green and low-carbon economies involved in the reaction have not been fully realized due to the harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%